Deconstruction and Normalization of Omah Rembug Adil as A Manifestation of Restorative Justice Based on the Local Wisdom of the Javanese People: Case Study of Sendang Village, Wonogiri Sub-District, Wonogiri District - Wahyu Beny Mukti Setiyawan; Majora Nuansa Al-Ghin; Yadi Suryadi; Fathurrahman Prasetyo Aji; Muhammad Wildan Khunaefi (Activa Yuris: Jurnal Hukum, 2023)
Solving problems through legal channels is a normal part of Indonesian cosmology today. Even so, the purpose of legal justice which should provide peace and justice to both parties has not really been realized. Therefore, taking the case study of Sendang Village as a pilot project for the Village Restorative Justice project from the High Court and the State Prosecutor's Office. Even though Sendang village has made good progress in implementing restorative justice through "Omah Rembug Adil", in fact "Omah Rembug Adil" is experiencing obstacles due to the cosmology of the people of Sendang and Wonogiri villages who are familiar with legal channels as a settlement solution. Thus, this study discusses Jacques Derrida's concept of deconstruction and Michel Foucault's normalization to create a normality of restorative justice cosmology. Using qualitative methods and Participatory Rural Appraisal (PRA) from April to June 2023 as an effort to map problems and potential local philosophies, this study has found that Javanese philosophy which is strong enough can be used as a tool in deconstructing and normalizing the cosmology of restorative justice for the people of Sendang village and Wonogiri. The implication can be carried out through the socialization of Javanese philosophy in the context of restorative justice. The form is seminars or FGDs targeting adults and youth, while [e-]comics for gen-z and millennials will be uploaded on various social media channels or formal education. Thus, this study succeeded in discussing the implication of solutions to the problems found by the "omah rembug adil"